2013
DOI: 10.1063/1.4798975
|View full text |Cite
|
Sign up to set email alerts
|

Gas-to-cluster effects in S 2p-excited SF6

Abstract: High resolution X-ray spectroscopic studies on free SF6 molecules and SF6 clusters near the S 2p ionization thresholds are reported. Spectral changes occurring in clusters for the intense molecular-like S 2p1/2,3/2 → 6a1g-, 2t2g-, and 4eg-resonances are examined in detail. Neither gas-to-cluster spectral shifts nor changes in peak shape are observed for the pre-edge 6a1g-band. Significant changes in band shape and distinct gas-to-cluster shifts occur in the S 2p1/2,3/2 → 2t2g- and 4eg-transitions. These are fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…The observed large HAP-tobone red shift δE P3s ≈0.9 eV confirms its relation with the effect of super periodicity on the band structure of HAP. This assignment is also supported by the recent investigation [67], where it is shown that, in contrast to the shape resonances, the pre-edge states in molecular solids and crystals containing chemical stable molecular-like groups demonstrate minor sensitivity to the surroundings of the core-excited atom.…”
Section: P 2p Edgesupporting
confidence: 64%
See 1 more Smart Citation
“…The observed large HAP-tobone red shift δE P3s ≈0.9 eV confirms its relation with the effect of super periodicity on the band structure of HAP. This assignment is also supported by the recent investigation [67], where it is shown that, in contrast to the shape resonances, the pre-edge states in molecular solids and crystals containing chemical stable molecular-like groups demonstrate minor sensitivity to the surroundings of the core-excited atom.…”
Section: P 2p Edgesupporting
confidence: 64%
“…The P / / -2p 1 3 2,1 2 e * and t 2 * states located above the edge are usually attributed to the shape resonances (see, e.g. [67]). The P 2p NEXAFS of native and heated bone and HAP [31,53] provides an additional sensitive probe of the hierarchy induced changes in electronic structure of bone tissue.…”
Section: P 2p Edgementioning
confidence: 99%
“…The nearly Gaussian shape of the Ca 2+ 2p 3/2 −1 and 2p 1/2 1 PE lines is associated with the bandwidth of the photon source, the inhomogeneous imperfectness and size distribution of crystallites as well as with the quadratic intra-and intercrystallite displacements. 35 The extracted Gaussian widths W G are given in parenthesis in Table 1. The Lorentzian widths are about 0.1 eV and can be reasonably assigned with the Ca 2+ 2p-hole live time.…”
Section: General Remarksmentioning
confidence: 99%
“…The contributions of asymmetric Lorentzian associated with the PE trapping time (the multiple scattering effects) 35 are negligibly weak.…”
Section: Characteristicsmentioning
confidence: 99%